2007
DOI: 10.1002/cb.210
|View full text |Cite
|
Sign up to set email alerts
|

Who are organic food consumers? A compilation and review of why people purchase organic food

Abstract: This paper integrates and synthesizes the findings of published research on organic food consumption. We identify several themes that reflect the various rationales used by consumers when deciding to purchase organic food. The literature clearly indicates that the word ''organic'' has many meanings, that consumers of organic foods are not homogeneous in demographics or in beliefs, and that further research could help better describe the various constituencies that are often lumped together as ''organic food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

81
1,089
6
66

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,324 publications
(1,242 citation statements)
references
References 39 publications
81
1,089
6
66
Order By: Relevance
“…Studies reporting sociodemographic and lifestyle differences between non-organic food consumers and frequent organic consumers are plentiful (6,25,30,(44)(45)(46)(47)(48)(49) and one was conducted in the NutriNet-Santé cohort (28) . Consistent with previous studies (25,45,(47)(48)(49) , we found herein that income seemed to be a weak determinant compared with education to explain differences in organic food consumption behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting sociodemographic and lifestyle differences between non-organic food consumers and frequent organic consumers are plentiful (6,25,30,(44)(45)(46)(47)(48)(49) and one was conducted in the NutriNet-Santé cohort (28) . Consistent with previous studies (25,45,(47)(48)(49) , we found herein that income seemed to be a weak determinant compared with education to explain differences in organic food consumption behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this increased attention of governments, the expansion of demand for organic foods in France over the past decades (3,4) is also largely driven by consumers' beliefs of the health benefits of organic foods (5)(6)(7)(8)(9) . Consumers are becoming more and more demanding with regard to the quality and safety of foods, which they want to have high nutritional values and be pesticide free (10) .…”
mentioning
confidence: 99%
“…Although the number of studies modelling consumer behaviour in the organic market is considerable 5,6 , the debate on determinants of organic food consumption provides conflicting evidence. In this context, two main aspects have characterised research concerning organic food consumption: (i) investigations focus mainly on analysing consumer behaviour in mature organic markets and studies considering emerging organic markets are limited mostly to Asian countries [7][8][9][10][11][12][13] ; and (ii) cross-country studies comparing mature and emerging organic markets are quite rare 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…It is thus assumed that consumer intention will also influence stated behaviour of organic food consumption in Germany and Chile. However, there are several barriers, or as Ajzen calls them, perceived behavioural controls, reported by scholars that hamper behaviour and can also have an impact on individuals' intentions and behaviour 6,18,43,55 . Following the body of literature addressing organic food consumption, the effect of premium prices, lack of information, scepticism and lack of convenience on consumer intention and behaviour is tested.…”
mentioning
confidence: 99%
“…La question est donc de savoir si, compte tenu des évolutions des comportements des consommateurs, le fait régional constitue un avantage supplémentaire pour les produits biologiques. D'un point de vue académique il existe un grand nombre de travaux concernant les déterminants de l'intention d'achat de produits biologiques ainsi qu'en attestent les deux dernières revues sur le sujet (Hughner et al, 2007, Aertsens et al, 2009. Parmi ces motivations celles liées aux bénéfices attendus en termes de santé et de protection de l'environnement restent prédominantes.…”
unclassified